2010
DOI: 10.1016/j.dnarep.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the live cell DNA marker DRAQ5 on chromatin-associated processes

Abstract: Influence of the live cell DNA marker DRAQ5 on chromatin-associated processes. DNA Repair, 9 (7). pp. 848-855.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…EMT has also been demonstrated to play an essential role during the formation of cancer stem cells [79]. Previously, we confirmed that PGCCs can be induced by CoCl 2 and paclitaxel.…”
Section: The Role Of Emt In the Process Of Tumor Budding And Pgccssupporting
confidence: 77%
“…EMT has also been demonstrated to play an essential role during the formation of cancer stem cells [79]. Previously, we confirmed that PGCCs can be induced by CoCl 2 and paclitaxel.…”
Section: The Role Of Emt In the Process Of Tumor Budding And Pgccssupporting
confidence: 77%
“…Indeed, despite initial promise of DRAQ5 in live-cell-imaging applications, [53,54] recent studies have highlighted the ability of this organic intercalator to induce DNA damage and impact cell viability. [56,57] To assess live-cell uptake and cellular localisation of each complex, HeLa cells were incubated with 3 and 4 at sub-cytotoxic levels before visualization with fluorescent (confocal) microscopy. The observation of intracellular 3 MLCT-based emission confirms that the complexes are internalized by live HeLa cells ( Figure 6).…”
Section: Cellular Imagingmentioning
confidence: 99%
“…In addition, a 12‐fold decrease in cMyc transcripts accumulation is observed 4 h after DRAQ5 incubation with U2OS cells. In human fibroblasts (MRC5SV) after 1 h incubation DRAQ5 inhibits [H3] incorporation (15). In U2OS cells carrying a gene array, within minutes after DRAQ5 addition, we show that transcripts disappear from the transcription site.…”
Section: Discussionmentioning
confidence: 99%